Biocommunication in soil microorganisms - Witzany, Günther; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Communication is defined as an interaction between at least two living agents which share a repertoire of signs. These are combined according to syntactic, semantic and context-dependent, pragmatic rules in order to coordinate behavior. This volume deals with the important roles of soil bacteria in parasitic and symbiotic interactions with viruses, plants, animals and fungi. Starting with a general overview of the key levels of communication between bacteria, further reviews examine the various aspects of intracellular as well as intercellular biocommunication between soil microorganisms. This includes the various levels of biocommunication between phages and bacteria, between soil algae and bacteria, and between bacteria, fungi and plants in the rhizosphere, the role of plasmids and transposons, horizontal gene transfer, quorum sensing and quorum quenching, bacterial-host cohabitation, phage-mediated genetic exchange and soil viral ecology.
Communication among Phages, Bacteria, and Soil Environments, Stephen Abedon -- Soil Bacteria and Bacteriophages, Robert Armon -- Soil phage ecology: Abundance, Distribution, and Interactions with Bacterial Hosts, Kurt E. Williamson -- Identification and Analysis of Prophages and Phage Remnants in Soil Bacteria, K.V. Srividhya and S. Krishnaswamy -- Back to the Soil: Retroviruses and Transposons, Omar Bagasra, D. Gene Pace -- Ubiquitous Bacteriophage Hosts in Rice Paddy Soil, Makoto Kimura*, Guanghua Wang, Susumu Asakawa -- Phage Biopesticides and Soil Bacteria: Multilayered and Complex Interactions, Antonet Svircev, Susan Lehman, Peter Sholberg, Dwayne Roach, Alan Castle -- Interactions between bacteriophage DinoHI and a network of integrated genetic elements which control virulence in Dichelobacter nodosus, the causative agent of ovine footrot, Brian Cheetham, Gabrielle Whittle, Michael Ting, Margaret Katz -- Gene Network Holography of the Soil Bacterium Bacillus subtilis, Dalit Roth, Asaf Madi, Dror Y. Kenett, Eshel Ben-Jacob -- The Core Genome Concept Applied to Soil Bacteria, Margaret Riley -- Plasmids of Rhizobiaceae and their role in interbacterial and transkingdom interactions, Katherine Pappas, Miguel Cevallos -- Quorum sensing and quorum quenching in soil ecosystems, Yves Dessaux, Emilie Chapelle, Denis Faure -- Integration of cell-to-cell signals in soil bacterial communities, Max Teplitski, Massimo Merighi, Mengsheng Gao, Jayne Robinson -- Beneficial rhizobacteria induce plant growth: mapping signaling networks in Arabidopsis, Huiming Zhang, Mina Aziz, Xitao Xie, Mi-Seong Kim, Xin Shen, Paul W. Paré -- Signal and nutrient exchange in the interactions between soil algae and bacteria, Max Teplitski, Sathish Rajami -- Communication among soil bacteria and fungi, Ilona Pfeiffer -- Microbe?microbe, microbe-plant biocommunication, Ralf Oelmüller, Neeraj Shrivastava, Meghna Pohani, Kailash C Upadhayaya, Irena Sherameti, Paul Murugan, Shashibala Singh and Ajit Varma.
Electronic reproduction.
Keywords: Soil microbiology; Cell interaction; Electronic books